Water Balance Study of Tonle Bati Irrigation Project, Cambodia - Chreang, Leng (1999)
This study on water balance in the paddy field was done to determine crop evapotranspiration and water use efficiency. The experiment was conducted during the main season for three rice varieties, namely: Phcar Khney, Kung Sor and IR66. All varieties were nursed and transplanted in three adjacent plots. Three plots, 100 square meters each, were prepared in a large paddy field. The transplanting spacing in the experimental plots was 20x20 cm and the number of seedlings per hill was 3. The results obtained on seasonal water requirement for evapotranspiration varied with varieties. They were 680, 771 and 454 mm for Phcar Khney, Kung Sor, and IR66, respectively. Daily average evapotranspiration was 6.1 mm/day throughout the season for all varieties. Water use efficiency was calculated by using equation (ETc + S&P)/(IR + RF). The results obtained ranged from 50% to 71%, or an average of 63% for the three plots. For an area, where lateral seepage is negligible, the water use efficiency should be 60% for wet season rice.